PENGARUH PENERAPAN TEKNIK IDENTITAS KORPORAT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 1 KOTO SALAK KABUPATEN DHARMASRAYA - Asmara, Dwi Novri (Pendidikan Matematika, 2014)
The background of this research is that the students were passive and afraid toexplore their opinion and ideas that they have and their math conceptunderstanding was low. The aim of this research was to find out is the studentsâlearning activity during the implementation of corporate identity technique betterthan the implementation of convention technique at the seventh grade students ofSMPN 1 Koto Salak. The design of this research is experimental research design.Based on the analysis of observation sheets, the studentsâ learning activitiesimproved. The result of hypothesis testing by using t-test supported by MINITABsoftware shown that the P-value = 0,002 smaller than = 0, 05. Therefore, itcan be learning activities of students in the experimental class of the first meetingup to five experiencing have developmental activities and the studentsâ mathconcept understanding of seventh grade students of SMPN 1 Koto Salak improvedby implementing corporate identity technique in teaching learning process ofmath.